(untitled) (New York, 2007)
This contribution to Palgrave's 'Advances' series addresses a wide range of issues that have arisen in post-Gricean pragmatic theory, in chapters by distinguished authors. Among the specific topics covered are scalar implicatures, lexical semantics and pragmatics, indexicality, procedural meaning, the semantics and pragmatics of negation. The volume includes both defences and critiques of Relevance Theory and of Neo-Gricean Pragmatics.
Keywords: Pragmatics